Cancer-associated acinar-to-ductal metaplasia within the invasive front of pancreatic cancer contributes to local invasion. (1st March 2019) - Kibe, Shin; Ohuchida, Kenoki; Ando, Yohei; Takesue, Shin; Nakayama, Hiromichi; Abe, Toshiya; Endo, Sho; Koikawa, Kazuhiro; Okumura, Takashi; Iwamoto, Chika; Shindo, Koji; Moriyama, Taiki; et al.
Abstract: The pancreas is an organ prone to inflammation, fibrosis, and atrophy because of an abundance of acinar cells that produce digestive enzymes. A characteristic of pancreatic cancer is the presence of desmoplasia, inflammatory cell infiltration, and cancer-associated acinar atrophy (CAA) within the invasive front. CAA is characterized by a high frequency of small ducts and resembles acinar-to-ductal metaplasia (ADM). However, the clinical significance of changes in acinar morphology, such as ADM with acinar atrophy, within the tumor microenvironment remains unclear. Here, we find that ADM within the invasive front of tumors is associated with cell invasion and desmoplasia in an orthotopic mouse model of pancreatic cancer. An analysis of resected human tumors revealed that regions of cancer-associated ADM were positive for TGFα, and that this TGFα expression was associated with primary tumor size and shorter survival times. Gene expression analysis identified distinct phenotypic profiles for cancer-associated ADM, sporadic ADM and chronic pancreatitis ADM. These findings suggest that the mechanisms driving ADM differ according to the specific tissue microenvironment and that cancer-associated ADM and acinar atrophy contribute to tumor cell invasion of the local pancreatic parenchyma. Highlights: Cancer-associated acinar atrophy is observed within the invasive front of pancreatic cancer. Cancer-associated acinar atrophy is characterized by a high frequency of ADM. The morphological changes in acini via ADM contribute to desmoplasia and cancer cell invasion of the local parenchyma . The mechanisms driving ADM differ according to the given microenvironment.